Inkjet‐Printed Cu(2)ZnSn(S, Se)(4) Solar Cells - Lin, Xianzhong (Adv Sci (Weinh), 2015)
Cu(2)ZnSn(S, Se)(4)‐based solar cells with total area (0.5 cm(2)) power conversion efficiency of 6.4% are demonstrated from thin film absorbers processed by inkjet printing technology of Cu‐Zn‐Sn‐S precursor ink followed by selenization. The device performance is limited by the low fill factor, which is due to the high series resistance. [Image: see text]